SAT0507 Growth and Weight Gain in Children with Juvenile Idiopathic Arthritis: Results from the Reacch-Out Cohort. (9th June 2015) - Guzman, J.; Kerr, T.; Ward, L.; Ma, J.; Oen, K.; Boire, G.; Feldman, B.; Scuccimarri, R.; Houghton, K.; Bruns, A.; Dancey, P.; Rosenberg, A.; et al.
Abstract : Objectives: To determine 1) height, weight and BMI trajectories in children with juvenile idiopathic arthritis (JIA) in a contemporary cohort; 2) their risk of growth delay, short stature, weight gain and obesity; and 3) the impact of disease activity and corticosteroid use on growth and weight gain. Methods: 1154 children newly diagnosed with JIA from 2005 to 2010 at 16 Centres in the Research in Arthritis in Canadian Children emphasizing Outcomes (ReACCh-Out) inception cohort were included. Height and weight measurements scheduled at 0, 6, 12, 18, 24, 36, 48 and 60 months after enrolment were used to calculate age and sex standardized Z-scores for height, weight and body mass index (BMI). Locally weighted scatter plot smoothing was used to display mean Z-score trajectories. Growth delay meant a decrease of 1.0 height Z-scores or more from the child's baseline. Short stature meant a height below the 2.5th percentile for age and sex. Weight gain meant an increase of 1.0 BMI Z-scores or more from the child's baseline. Obesity meant a BMI above the 95th percentile for age and sex. The cumulative incidence of growth delay, short stature, weight gain and obesity was estimated with Kaplan Meier survival methods. The impact of disease activity and corticosteroid use on Z-scores was estimated with mixed effects models. Results: Median age at diagnosis was 9.5 years (IQR 4, 13) and 64% were female. Median follow-up was 35.5 months (23, 49). Mean height Z-scores remained stable in children with enthesitis related, oligoarthritis and undifferentiated JIA. They decreased markedly in systemic JIA (from +0.2 to -0.3). In other categories, they decreased mildly during the first year and recovered afterwards. Mean BMI Z-scores increased in children with systemic JIA and RF-positive polyarthritis, decreased slightly in psoriatic arthritis and remained stable in other categories. At enrolment, the prevalence of short stature was 2.5% and the prevalence of obesity was 16%. The cumulative incidences of new-onset growth delay, short stature, weight gain and obesity within 3 years of diagnosis were 8.9% (95% CI 7.1-11.0), 3.1% (2.1-4.4%), 10.4% (8.6-12.6) and 10.5% (8.6-12.9), respectively. These were higher in systemic JIA (Figure ) at 24.4% (15.3-37.5), 10.5% (5.1-20.8), 28.2% (19.1-40.5) and 34.7% (23.2-49.9), respectively. Systemic corticosteroids were prescribed for 85.5% of children with systemic JIA. One mg/kg of prednisone corresponded to a mean height decrease of 0.48 Z-scores (0.29-0.68) and a mean BMI increase of 0.45 Z-scores (0.25-0.65). After adjusting for prednisone dose, an increase of 1 cm in the physician global assessment of disease activity corresponded to a mean decrease of BMI of 0.023 Z-scores (0.006-0.039), with no effect on height (p=0.42). Conclusions: The impact on growth and weight gain was marked in children with systemic JIA and those who received systemic corticosteroids. For most other children, growth and weight gain were similar to what is seen in the general population. Disclosure of Interest: None declared